Developing the public attitudes about addiction instrument. (April 2015) - Broadus, Angela Doreen; Evans, William P.
Abstract Using a series of three studies, this project developed an addiction attitudes instrument for use in the general population and completed a preliminary analysis of the moderators of addiction attitudes. The final 54-item instrument has five subscales representing five models of addiction theory: Moral Model, Nature Model, Psychological Model, Sociological Model, and Disease Model. These models differ in beliefs about abuse and addiction aetiology, rationale for behaviour and prognosis for change. Development of the instrument included an inductive, ground-up approach using focus group participants from metropolitan areas in a western US state, and a deductive, top-down approach with experts in the fields of survey development, attitudes and addiction providing input in generating the survey item pool. University students and a sample of state residents tested the draft instrument. Analysis of the moderators of attitudes about addiction suggested that gender, age, education, religious beliefs and addiction treatment history are important predictors of attitudes.